Hemorrhage-control Tourniquets: How Intuitive are They?. Issue Volume 34:Issue s1(2019) (May 2019) - Ochs, Nicole; Sexton, Martha; McKenzie, Nicole; Rega, Paul; Ziehr, Jonathon; Parquette, Brent; Fink, Brian
Abstract : Introduction: According to the Federal Bureau of Investigation (FBI), there were fifty active shooter incidents in 2016 and 2017. In the first five months of 2018, there have been 23 school shootings where someone was injured or killed. Hemorrhage-control tourniquets have proven their life-saving capability in the military and civilian EMS. Now, they are being advocated for use by civilians – the true "first responders." Since Combat Application Tourniquets (CATs) are strap-and-windlass devices, the question remains whether a naïve population can intuitively apply them efficaciously. Aim: To determine the efficacy (speed, correct placement) of a CAT by an interprofessional group of healthcare students naïve to tourniquet hemorrhage control. Methods: Consenting students attempted to apply a CAT to a standardized patient with a simulated hemorrhaging brachial artery. No instruction was given except for the directions included in the package. Timing began upon removal of the tourniquet from the package and ended when the participants stated they completed their attempt. Errors in application were documented. Afterward, students received education and an opportunity to properly re-apply the tourniquet. The completion times of the students were compared to ten emergency medical technicians (EMT-P), serving as subject matter experts. Errors in application were categorized. Results: 50 students from the following professions participated: Medicine, Nursing, Public Health, and Respiratory Therapy. The mean time of tourniquet application was 96.16 seconds (range: 25.12-226.31). This was statistically different from the EMT-Ps' time of 42.83 seconds (range: 23.89-82.94). Additionally, only five (10%) placed the tourniquet correctly. Errors included improper location and windlass misuse or non-use. The instructions were frequently critiqued for being difficult to read and containing confusing graphics. Discussion: Provision of commercial tourniquets in public access areas must be accompanied by civilian education and the creation of CAT instructions that are simplistic, comprehensible, and suitably graphic.